2018
DOI: 10.2174/1381612824666180302141902
|View full text |Cite
|
Sign up to set email alerts
|

Novel Optical Techniques for Imaging Microcirculation in the Diabetic Foot

Abstract: Although promising, the currently available novel optical techniques need to be further improved technically and prospective trials are necessary to evaluate their clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…Next to this, Yang et al 58 found that the degree of PWS blanching correlates well to the decrease in perfusion measured by LSCI. Finally, as pointed out by Mennes et al, 59 LSCI could be of help in the assessment of diabetic foot ulcers that are related to local ischemia. They point out that no such study has yet been performed on the diabetic foot population even though there seems to be a lot of potential based on a comparable study by others.…”
Section: Dermatologymentioning
confidence: 86%
“…Next to this, Yang et al 58 found that the degree of PWS blanching correlates well to the decrease in perfusion measured by LSCI. Finally, as pointed out by Mennes et al, 59 LSCI could be of help in the assessment of diabetic foot ulcers that are related to local ischemia. They point out that no such study has yet been performed on the diabetic foot population even though there seems to be a lot of potential based on a comparable study by others.…”
Section: Dermatologymentioning
confidence: 86%
“…However, clinicians are not able to assess the structural or physiological information of DFU by visual inspection. The assessment for ischemia in such cases can also be assessed by ankle brachial indexes and clinical examination along with Doppler ultrasound and toe pressures measurements . In all these cases, the key marker of healing status‐perfusion is not assessed in an objective way.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry and oral science LSCI has been applied to image the gingival blood flow, dental pulp flow. 41,42 In cardio vascular studies there are numerous uses of LSCI. A study was published regarding the evaluation of the forearm endothelium presenting notably impaired vasodilatory response with type I diabetic patient.…”
Section: Other Application Of Lscimentioning
confidence: 99%